KOMPOSISI DAN LUAS RELUNG MAKANAN IKAN KEPERAS (Cyclocheilichthys apogon, Valenciennes, 1842) DI SUNGAI MUSI [Food composition and niche breadth of beardless barb (Cyclocheilichthys apogon, Valenciennes, 1842) in Musi River] - Dimas Angga Hedianto; Ridwan Affandi; Siti Nurul Aida (Jurnal Iktiologi Indonesia, 2010)
Objective of the research was to analysis food habits of beardless barb (Cyclocheilichthys apogon) with observing a composition of prey items. Research was carried out in June 2006, August 2006, and January 2007 in Musi River alongside the upstream and downstream using cast net and experimental gillnet. Stomach content analysis was based on index of preponderance and niche breadth. Beardless barb analyzed during research about 159 individuals fish with total length ranging from 57-175 mm and weight ranging from 1.88-71.79 gram. Beardless barb is omnivorous having the character of euryphagic with plant (54.98) as basic food; detritus (19.05), worm (9.30), phytoplankton (8.22), insect (4.89) as secondary food; and zooplankton (3.57%) as supplement food. Difference of sex, size, habitat, and research time did not cause change and difference of resources utilization by beardless barb in the Musi River. Female of beardless barb in upstream Musi River has different resources utilization with increasing of resources utilization of animal organism which is estimated to has relation of requirement of reproduction energy. Equality of resources (food organism) which utilization by beardless barb in various sex and size, was conducive existence of emulation when food resources in limited condition.